Money, the financial system, and economic policy - Cooper, S. Kerry; Fraser, Donald R. ;Uselton, Gene C. (Reading, Massachusetts : Addision-Wesley Publishing Company, 1983)
This book offers a comprehensive treatment of the material traditionally associated with the introductory college course in money and banking. It includes thorough coverage of monetary theory and economic policy as well as description and analysis of the instruments, institutions, and markets that comprise the monetary-financial system. The sequencing and selection of chapters can be adapted to suit the background of students and the emphasis and orientation of the instructor. The text material is presented in a straightforward manner. While the book employs diagrammatic models (the conventional IS-LM analysis and an aggregate demand-aggregate supply model for expository Purposes in the coverage of macroeconomic relationships, all diagrams are fully explained in words. The approach and material treatment reflect the authors' goal of writing a highly readable, interesting, and instructive book not of impressing colleagues with scholarly presentation of esoteric exposition. We have at- tempted to provide thorough and complete treatment of the monetary-financial system and develop analytical concepts that students will find useful in understanding, analyzing, and interpreting economic phenomena. All technical terms are set in boldface type when introduced and are carefully defined. Often they are redefined when employed in subsequent chapters. Such emphasis on definition of technical terms facilitates altering the chapter sequence and helps students develop a thorough grasp of relevant terminology.
Money and Financial Intermediation -- The Financial System -- Central Banking and Monetary Control -- Monetary Theory and Economic Policy -- International Dimensions of Economic Policy -- The Record of Economic Policy.
Includes bibliographical references and index.
Keywords: BANK -- FINANCE